Development evaluation in authoritarian states: A case from Kazakhstan. (17th August 2020) - Knox, Colin
Abstract: Motivation: Authoritarian states receive development funding from international donors for programmes and interventions, some aimed at improving their governance systems. This article reports on the evaluation of an EU‐funded programme in Kazakhstan, seen as the most progressive reformer in Central Asia. The EU Programme was aimed at enhancing Kazakhstan's business competitiveness through better regulation and civil service modernization. Purpose: This article addresses two research questions. What was the impact of the EU‐funded intervention? What role, if any, did the evaluation play in reflective policy learning for the future? Approach and Methods: The research draws on quantitative and qualitative evidence. This involved analysing secondary data sources on the effectiveness of governance over time in Kazakhstan and interviews for 34 key stakeholders on the impact of the EU interventions. Findings: We find no significant improvements in governance over time. While the donor responded in a flexible way to meet the changing strategic goals of the state (which were at the personal behest of the President), this did not help to embed evaluation as part of the policy cycle for future learning. The key beneficiary here was the Government of Kazakhstan. Policy implications: Wider systemic change from upward accountability to downward accountability to citizens is needed to make evaluation relevant for authoritarian states. Upward accountability to the President is a feature of authoritarian regimes, which precludes citizens from being able to hold the state to account. Without these systemic changes, autocracies simply engage in development evaluation as a perfunctory exercise to meet donor requirements.